“Capricorn Concerto” by Samuel Barber: Content and Genre-Style Dimensions - Antonova, Olena (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2021)
Relevance of the study. Samuel Barber’s musical legacy is unevenly covered in musicological literature, in particular, “Capricorn Concerto” is on the periphery of scientific attention — the work that is not only bright and interesting, but also indicative of the composer’s creativity as a whole. In addition, researchers, as a rule, do not associate the semantic and stylistic features of a concert with its genre specificity, which ultimately determines the integrity of the artistic structure. The main objective of the study is to identify the relationship between genre, style and content parameters of Capricorn Concerto. The methodology of the research includes the historical and biographical approaches used to study the circumstances of S. Barber’s life and creativity during the period of work on the “Capricorn Concerto”, as well as structural-functional, genre-style and intonational-dramatic methods necessary for a comprehensive analysis of this work. Results and conclusions. “Capricorn Сoncerto” by S. Barber is considered in the unity of content, style and genre characteristics. The existing hypotheses about the links between the program content of the work and the name of the composer’s house in Mount Kisco are presented. The character and dramatic functions of musical themes representing the house and its inhabitants are analyzed, the idea of the personification of the wind instruments’ timbres and the reflection of the generalized program of the work through the game thematic logic and timbre dramaturgy is put forward. The stylistic influences in “Capricorn Сoncerto” are characterized. The connections with baroque music and the Brandenburg Concerto No. 2 by J. S. Bach, presented at the timbre, textured, compositional, intonation levels, as well as in the methods of melodic development, are traced. The unification of the Baroque style elements with modern means of musical expression, in particular those associated with the music of I. Stravinsky, is emphasized. The place of “Capricorn Сoncerto” in S. Barber’s concert legacy is designated. The correspondence of all his four concerts to the basic requirements of the genre is noted, and at the same time specificity of “Capricorn Сoncerto”, manifested in its instrumental composition (three solo wind instruments and a string orchestra), structural organization (subordination of the compositional structure to the through development of the concert principle of dialogue) and the ratio of parties (multilevel dialogical processes) is emphasized. The interrelation of content, style and genre features of “Capricorn Concerto” is substantiated. It is concluded that the most important intentions of S. Barber’s work are reflected in this work: careful preservation of genre traditions, genetic connection with the styles of previous eras, deeply hidden, but always tangible resonance between personal biography and creativity